Integrating Flipped Classroom with Snowballing: A Hybrid Approach for Active Learning in Engineering Education - Jadhav, Ketaki A.; Watharkar, Snehal R.; Nishandar, Arati S. (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
Active learning activities play a crucial role in today's world of education and beyond. In an age of constant distractions and shortened attention spans, active learning activities maintain students' attention better than traditional passive learning methods. This paper introduces a hybrid model that integrates the flipped classroom (FC) with the snowballing technique (FCS), combining pre-class self-learning with in-class collaborative group expansion. This innovative approach aims to foster collaboration, critical thinking, and knowledge retention among engineering students. Students begin by working individually on the given problem or topic, gradually forming groups. Despite extensive research on active learning, limited literature exists on the structured integration of the snowballing technique within a FC framework, particularly in engineering disciplines. This study addresses this gap by investigating the impact of this combined approach in the context of a VLSI testing and verification course, an undergraduate elective course in the third year of electronics engineering. A detailed methodology, supported by quantitative data, student feedback, and assessment results, underscores the approach's effectiveness.